2020
DOI: 10.1186/s12889-020-09284-2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in access to healthcare services for individuals with disorders of sex differentiation in Bangladesh: an analysis of regional representative cross-sectional data

Abstract: Background: Worldwide people in disorder of sex development (DSD) faces multiple barriers while seeking their social rights, particularly healthcare services. We aimed to explore the healthcare opportunities available to them, using patterns of healthcare utilization and difficulties faced by DSD population in accessing healthcare services in Bangladesh. Methods: Data from a total of 945 DSD population and 71 medical staff were analyzed, collected from three major divisions (Dhaka, Chittagong, and Rajshahi) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…These efforts will eventually lead the local government to increase its efforts in public service work and improve the efficiency of livelihood improvement. (5) In addition, we found no significant correlation between regional population size and LIE, a result that differs from the findings of some previous studies [55][56][57][58]. However, we can draw an important conclusion.…”
Section: Discussion Of Regression Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…These efforts will eventually lead the local government to increase its efforts in public service work and improve the efficiency of livelihood improvement. (5) In addition, we found no significant correlation between regional population size and LIE, a result that differs from the findings of some previous studies [55][56][57][58]. However, we can draw an important conclusion.…”
Section: Discussion Of Regression Resultscontrasting
confidence: 99%
“…Cao et al found empirically that the total population of a region was negatively associated with the efficiency of health services [56]. Khan et al argue that this negative correlation is mainly because, as the population size of a region increases, it negatively affects the equity and fairness of public services, and, by extension, service efficiency [57]. Mainardi et al further refined their analysis of the impact of total population size by arguing that increasing the population size of a region in education services will promote the efficiency of those services but will reduce the efficiency of healthcare services [58].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation